On the dynamics of unemployment in a developing economy: Colombia (2003)
This paper estimates an asymmetric error correction model to analyse the dynamic behaviour of the Colombian unemployment rate. It is found that wages above their long-run equilibrium level do increase unemployment, but wages below this level do not reduce it. This finding provides evidence of the existence of hysteresis in the Colombian unemployment rate.